Pharmacotherapy and Pharmacology Textbooks at Jordanian Universities: A Content Analysis Study of Drug Use During Pregnancy - Daghash, Rajaa M.; Al-Saideh, Munim A.; Daghash, Ayah M.; Mohammad, Beisan A.; Fino, Leen B. (Jordan Journal of Pharmaceutical Sciences, 2026)
Background: The education of pharmacists on the benefits and risks associated with medication use during pregnancy, as well as the utilization of drug information resources to counsel pregnant women, is of paramount importance. Aim: This study aimed to evaluate the adequacy of pharmacotherapy-related content in textbooks used by pharmacy colleges at Jordanian universities, particularly regarding drug use during pregnancy. Methods: In this feasibility study, a content analysis was performed to provide an in-depth analytical description of pharmacology and pharmacotherapy textbooks and course syllabi utilized by pharmacy colleges at Jordanian universities. Results: Three textbooks were analyzed, revealing inadequate coverage of key aspects related to pregnancy in pharmacology textbooks across all selected diseases. Only 5% of the diseases included pharmacologic therapy, contraindications, and drug effects on the fetus. Pharmacotherapy textbooks covered 21% of these aspects, addressing etiology, pathophysiology, diagnosis, non-pharmacological and pharmacological therapies, interactions, and contraindications for certain diseases. Reviewed course syllabi lacked any specific topics on pregnancy. Conclusion: Pharmacotherapy during pregnancy is insufficiently covered in current textbooks, highlighting the need to update pharmacy curricula to ensure comprehensive coverage and better prepare pharmacists to counsel pregnant women effectively.